2023
DOI: 10.1088/2515-7655/acc2e6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of light illumination on the surface structure of two-dimensional Ruddlesden–Popper perovskite in the fabrication process

Abstract: Two-dimensional Ruddlesden–Popper (2DRP) perovskites are promising owing to their excellent environmental stability and competitive efficiency. During the fabrication process, 2DRP perovskites were often unintentionally exposed to light in the laboratory. However, the influence of light illumination on the surface structure of 2DRP during fabrication is unclear. Herein, the photodegradation of 2DRP perovskite (phenethylammonium lead iodide, PEA2PbI4) is comprehensively investigated using X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…6,[46][47][48] Blue laser irradiation (k ¼ 405 nm, intensity ¼ 50 mW cm À2 ) was used to degrade the prepared PEA 2 PbI 4 films since a higher photon energy causes more significant degradation. 28,29 We also carefully controlled the irradiation time and dose of x-ray and UV sources to prevent undesired degradation of the PEA 2 PbI 4 samples during measurements (supplementary material Sec. 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6,[46][47][48] Blue laser irradiation (k ¼ 405 nm, intensity ¼ 50 mW cm À2 ) was used to degrade the prepared PEA 2 PbI 4 films since a higher photon energy causes more significant degradation. 28,29 We also carefully controlled the irradiation time and dose of x-ray and UV sources to prevent undesired degradation of the PEA 2 PbI 4 samples during measurements (supplementary material Sec. 3).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 However, ironically, photostability has become a major topic of discussion among researchers in the 2D perovskite research field, as it is a significant challenge to their application in optoelectronic devices. [28][29][30][31][32][33] For example, the daily used fluorescent lamps, which emit also high-energy photons at extremely low intensities, can rapidly degrade the surface structure of 2D RP perovskites. 29 In many reports, it has been also revealed that the high-energy light irradiation on perovskites can disrupt crystalline structures, leading to undercoordinated Pb states that impede carrier transport and cause substantial loss of photoluminescence (PL).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations